Targeted therapy in NPM1-mutated AML: Knowns and unknowns - Wang, Rong; Xu, Pan; Chang, Lin-Lin; Zhang, Shi-Zhong; Zhu, Hong-Hu (Frontiers in Oncology, 2022)
Acute myeloid leukemia (AML) is a heterogeneous disease characterized by malignant proliferation of myeloid hematopoietic stem/progenitor cells. NPM1 represents the most frequently mutated gene in AML and approximately 30% of AML cases carry NPM1 mutations. Mutated NPM1 result in the cytoplasmic localization of NPM1 (NPM1c). NPM1c interacts with other proteins to block myeloid differentiation, promote cell proliferation and impair DNA damage repair. NPM1 is a good prognostic marker, but some patients ultimately relapse or fail to respond to therapy. It is urgent for us to find optimal therapies for NPM1-mutated AML. Efficacy of multiple drugs is under investigation in NPM1-mutated AML, and several clinical trials have been registered. In this review, we summarize the present knowledge of therapy and focus on the possible therapeutic interventions for NPM1-mutated AML.